2017
DOI: 10.1007/s11517-017-1621-2
|View full text |Cite
|
Sign up to set email alerts
|

A wrist sensor and algorithm to determine instantaneous walking cadence and speed in daily life walking

Abstract: In daily life, a person's gait-an important marker for his/her health status-is usually assessed using inertial sensors fixed to lower limbs or trunk. Such sensor locations are not well suited for continuous and long duration measurements. A better location would be the wrist but with the drawback of the presence of perturbative movements independent of walking. The aim of this study was to devise and validate an algorithm able to accurately estimate walking cadence and speed for daily life walking in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…Furthermore, only configurations using sensors on the lower limbs have been tested in this study. Other configurations including those using sensors on the wrists, the chest, or the pelvis exist [ 21 , 53 ] but were not tested as we wished to analyze the paretic and non-paretic limbs separately. Finally, we evaluated a limited number of subjects and, since CP gait patterns are very heterogeneous, a larger number of participants, especially in the CP group with a high level of disability (GMFCS II-III), would permit to strengthen the conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only configurations using sensors on the lower limbs have been tested in this study. Other configurations including those using sensors on the wrists, the chest, or the pelvis exist [ 21 , 53 ] but were not tested as we wished to analyze the paretic and non-paretic limbs separately. Finally, we evaluated a limited number of subjects and, since CP gait patterns are very heterogeneous, a larger number of participants, especially in the CP group with a high level of disability (GMFCS II-III), would permit to strengthen the conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm was not validated for slow walking and achieved poor results for running segments of data. The study in [ 14 ] used a wrist worn accelerometer to estimate the walking cadence and speed in daily life walking in several environments. The study in [ 15 ] proposed the use of some particular points in the acceleration time series in order to detect steps at normal speeds.…”
Section: Related Workmentioning
confidence: 99%
“…Single body segment mounted IMUs (e.g., wrist or pelvis) are limited in calculation of certain STGPs such as number of steps, step cadence, or step distance which may not be adequate for clinical applications [ 26 , 27 ]. Incorporating IMUs on additional body segments (e.g., foot, shank, thigh, pelvis, or trunk) may provide access to additional gait metrics and improve gait characteristic predictions, especially for patient populations with pathologic movement characteristics [ 26 , 28 , 29 , 30 ]. Carcreff et al demonstrated that IMUs placed on the shank and thigh yielded more accurate predictions of stride time, length, and velocity compared to feet mounted IMUs for children with cerebral palsy, particularly for those patients with increased disability [ 29 ].…”
Section: Introductionmentioning
confidence: 99%